Persepsi pekerja terhadap keberkesanan latihan : satu kajian di perbadanan pembekalan letrik Sarawak (PPLS) - Mohd Noor, Yusoff (Universiti Malaysia Sarawak, (UNIMAS), 2005)
This study is aimed to investigate the factors that influence the effectiveness Of training in Sarawak Electricity Supply Cooperation (SESCO). Questionnaire were used to obtain the finding of this study. The respondent amount of this study was 30 and they have attended the Quality Work Groups training. The questionnaire that is used in this study divided into three section, section a: respondents' background, section b: level of the transfer of Quality Work Groups Training and section c: factors that influencing the transfer of Quality Training. The data was analyzed using the Statistical Package for the Social Sciences (SPSS). The researcher was used Pearson Correlation Test and Multiple Regression Analysis to test the hypotheses of this study. The implication of this study can help the organization to identify the factors that influence the transfer of Training. This study also would provide opportunity for the future researcher to increase the scope of research pertaining to the transfer of training.